TO EVALUATE THE EFFECT OF INTRALESIONAL VIT D-3 INJECTION IN CUTANEOUS WARTS - SINGH, VINEET; MUDASSIR, MOHAMMAD; YADAV, SUSHIL (International Journal of Current Pharmaceutical Research, 2026)
Objective: To study the demographic characteristics, clinical types, and treatment response patterns of patients with cutaneous warts attending a dermatology outpatient department. Methods: This was a descriptive observational study including patients diagnosed with cutaneous warts. Demographic details, clinical characteristics, including type, number, and duration of warts, and management outcomes were recorded. Treatment response was assessed based on clinical resolution following treatment sittings. Results: The study population comprised 51% females and 49% males, with a mean age of 28.83±9.53 years. The most affected age group was 21–30 years (42%). Palmar warts were the most common clinical type (42%), followed by verruca plana (29%) and plantar warts (27%). The mean number of warts was 5.43±2.36, and the mean duration of disease was 6.45±3.25 mo. Most patients required four treatment sittings (67%). Complete response was observed in 48% of patients, while 21% showed partial response and 31% had no response to treatment. Conclusion: Cutaneous warts predominantly affected young adults and presented with varied clinical morphology and lesion burden. Multiple treatment sittings were often required, with variable therapeutic responses. These findings highlight the chronic nature of cutaneous warts and the need for individualized management strategies.